1978
DOI: 10.1103/physrevc.18.2138
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear resonance fluorescence inBa136

Abstract: The resonant scattering of electron bremsstrahlung by an enriched sample of ' Ba has been studied for photon energies of up to 5 MeV. It provided estimates of the: radiative widths for 10 levels. Based on the relative yields at scattering angles of 96' and 126, unambiguous spin assignments were made to 5 of these levels. Where feasible, the yield measurements were supplemented by self-absorption data and by linear polarization studies. For the strongest excitation in "Ba, at 3.436 MeV, the resonance fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Therefore, the PDR is a challenge for theory in nuclear physics because one can expect a good description of the fragmentation of a collective mode without including any phenomenological parameters responsible for the resonance width. Thus, the comparison to experimental data makes it possible to determine whether the damping mechanism for a collective mode in many-body systems is well understood.The first evidence for strong low-lying E1 excitations in heavy nuclei located in the energy region 5-10 MeV indicating an additional structure beside the IVGDR in the E1 response of atomic nuclei was found three decades ago [1][2][3]. Recently, an experimental survey of the whole mass region has revealed that the PDR is a common excitation mode in most atomic nuclei [4,5].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the PDR is a challenge for theory in nuclear physics because one can expect a good description of the fragmentation of a collective mode without including any phenomenological parameters responsible for the resonance width. Thus, the comparison to experimental data makes it possible to determine whether the damping mechanism for a collective mode in many-body systems is well understood.The first evidence for strong low-lying E1 excitations in heavy nuclei located in the energy region 5-10 MeV indicating an additional structure beside the IVGDR in the E1 response of atomic nuclei was found three decades ago [1][2][3]. Recently, an experimental survey of the whole mass region has revealed that the PDR is a common excitation mode in most atomic nuclei [4,5].…”
mentioning
confidence: 98%
“…The first evidence for strong low-lying E1 excitations in heavy nuclei located in the energy region 5-10 MeV indicating an additional structure beside the IVGDR in the E1 response of atomic nuclei was found three decades ago [1][2][3]. Recently, an experimental survey of the whole mass region has revealed that the PDR is a common excitation mode in most atomic nuclei [4,5].…”
mentioning
confidence: 98%
“…As nuclei in the N = 82 region have relatively low lying 3~~ states with very strong (E3; 3~ -» 0+) transitions, many investigations on (2 + (g> 3~) states concentrate on different Ba, Ce, Nd, and Sm isotopes. In photon scattering experiments the 1~~ member of the 2 + ® 3~ multiplet has been found in various N = 82 nuclei [10][11][12][13]. Experimental effort is under way to detect other members of this multiplet with different experimental techniques, but the information is sparse; see, e.g., [14][15][16].…”
mentioning
confidence: 99%
“…This mode was first observed in neutron capture reactions [1][2][3] and from the beginning of the 1990s it has attracted considerable interest. Recently in the photon scattering experiments in N = 82 semi-magic 136 Xe, 138 Ba, 140 Ce, 142 Nd and 144 Sm nuclei a similar mode has been observed in the energy interval between 5.5 MeV and 8 MeV (see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…These observations initiated a large number of both experimental and theoretical research into the PDR. A series of subsequent nuclear experiments [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have shown that this is a common mode in nuclei at excitation energies around 7 MeV. Nowadays this mode has been found for isotopes ranging from the light nuclei (such as 17−22 O) up to lead isotopes including the transitional nuclei [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%